2018
DOI: 10.1002/brb3.1086
|View full text |Cite
|
Sign up to set email alerts
|

Estriol‐mediated neuroprotection in multiple sclerosis localized by voxel‐based morphometry

Abstract: IntroductionProgressive gray matter (GM) atrophy is a hallmark of multiple sclerosis (MS). Cognitive impairment has been observed in 40%–70% of MS patients and has been linked to GM atrophy. In a phase 2 trial of estriol treatment in women with relapsing–remitting MS (RRMS), higher estriol levels correlated with greater improvement on the paced auditory serial addition test (PASAT) and imaging revealed sparing of localized GM in estriol‐treated compared to placebo‐treated patients. To better understand the sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 92 publications
1
20
0
Order By: Relevance
“…Nonetheless, the enrichment of immune-associated pathways points to a possible anti-inflammatory activity of the candidate drugs. Interestingly, the following drugs have been reported to have neuroprotective activity: fluocinonide 59 , kawain 6063 , allantoin 64 , dipyridamole 6567 , estriol 68 , levamisole 69 , mycophenolic acid 70 , neostigmine 71 , probenecid 72,73 , chlorpromazine 74 , and phenoxybenzamine 75 , and xamoterol has been reported to ameliorate neuroinflammation and pathology in 5xFAD mice 76 and shown to enhance cognition in a Down syndrome mouse model 77 . The atypical antipsychotic risperidone prescribed to manage psychosis in AD has demonstrated neuroprotection in animal models of ischemia 78 .…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the enrichment of immune-associated pathways points to a possible anti-inflammatory activity of the candidate drugs. Interestingly, the following drugs have been reported to have neuroprotective activity: fluocinonide 59 , kawain 6063 , allantoin 64 , dipyridamole 6567 , estriol 68 , levamisole 69 , mycophenolic acid 70 , neostigmine 71 , probenecid 72,73 , chlorpromazine 74 , and phenoxybenzamine 75 , and xamoterol has been reported to ameliorate neuroinflammation and pathology in 5xFAD mice 76 and shown to enhance cognition in a Down syndrome mouse model 77 . The atypical antipsychotic risperidone prescribed to manage psychosis in AD has demonstrated neuroprotection in animal models of ischemia 78 .…”
Section: Resultsmentioning
confidence: 99%
“…While the type of oestrogen preparation does matter in terms of potential impact in multiple sclerosis, oestriol was shown to be immunomodulatory ( Soldan et al , 2003 ; Gold et al , 2009 ) and to reduce number of enhancing lesions ( Sicotte et al , 2002 ). In a multicentre phase 2 trial, higher oestriol levels were associated with a reduction in relapses, cognitive improvement and dampening of cortical grey matter atrophy ( Voskuhl et al , 2016 ; MacKenzie-Graham et al , 2018 ). Of course, such a neuroprotective effect cannot be suggested as being multiple sclerosis specific.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that cognitive disability in particular may be worse in males as compared to females with MS [25], and differences in atrophy of major GM structures have been correlated with cognitive disability [28,54,[59][60][61][62][63]. Further studies are needed comparing MS women and MS men using biology-driven functional connectivity analysis [26, and voxel-wise mapping of localized GM atrophy aligned with cognitive disability [30,31]. Sex differences in other disabilities such as in walking or vision, for example, should also be mapped to contrast with cognitive disability maps.…”
Section: Correlations Between 9hpt and Subcortical Gm Volumesmentioning
confidence: 99%
“…Brain atrophy, specifically gray matter (GM) atrophy, serves as a putative surrogate for neurodegeneration in MS. Regional differences in GM atrophy have been shown in MS, and clinical disabilities have been shown to correlate with GM atrophy in clinically eloquent neuroanatomic regions [27][28][29][30][31]. Regional differences in gene expression in astrocytes, microglia, and oligodendrocytes have also been shown in both health and disease [32][33][34][35], including a sex-specific astrocytic response to injury in an MS model [36].…”
Section: Introductionmentioning
confidence: 99%